Design of Interlocking for the Micro Unmanned Aerial Vehicle Vertical Take-Off and Landing Mechanism - Ahmad Wazini Bin Ahmad Tajuddin, Ahmad Wazini (Universiti Teknologi Petronas, 2010)

(untitled)
This report is written for the purpose of highlighting the result of the analysis and simulation after some background research for the project titled Design of Interlocking for the Micro Unmanned Aerial Vehicle Vertical Take-Off and Landing Mechanism. This report also details the scope of study, research methods, literature review and outcome of the project.